New FES-Assisted Knee Swinging Ergometer for Stroke Patient: A Design and Simulation Study - Boudville, R.; Hussain, Z.; Yahaya, S. Z.; Noor, M. H. M. (Elektronika ir Elektrotechnika, 2014)
This paper presents the development of a model of knee swinging ergometer for stroke patient. Knee swinging ergometer is introduced as a hybrid exercise for restoration of function of the knee for stroke patients through the application of functional electrical stimulation. The aim of the new FES-assisted knee swinging ergometer is to provide high intensity exercise. This will elongate the exercise duration and avoid early muscle fatigue. The ergometer is designed to utilize the voluntary non-paretic leg movement in assisting the FES-induced paretic leg of stroke patient. A humanoid with muscle model was developed and incorporated with the ergometer to perform simulation of FES-assisted knee swinging exercise. PID controller is used to achieve full knee extension during each cycle of knee swinging exercise. Simulation results show that the ergometer is able to reduce half of the required electrical stimulation. In conclusion, the new knee swinging ergometer is able to avoid early muscle fatigue in performing high intensity knee exercise through electrical stimulation. DOI: http://dx.doi.org/10.5755/j01.eee.20.1.6168